You Are a Badass: How to Stop Doubting Your Greatness and Start Living an Awesome Life - Jen Sincero (Philadelphia Running Press, 2013)
In this refreshingly entertaining how-to guide, #1 New York Times Bestselling Author and world-traveling success coach, Jen Sincero, serves up 27 bite-sized chapters full of hilariously inspiring stories, sage advice, easy exercises, and the occasional swear word. If you're ready to make some serious changes around here, You Are a Badass will help you: Identify and change the self-sabotaging beliefs and behaviors that stop you from getting what you want, blast past your fears so you can take big exciting risks, figure out how to make some damn money already, learn to love yourself and others, set big goals and reach them - it will basically show you how to create a life you totally love, and how to create it now. By the end of You Are a Badass, you'll understand why you are how you are, how to love what you can't change, how to change what you don't love, and how to use The Force to kick some serious ass.
Keywords: Nonfiction; Self Help; Personal Development